2006
DOI: 10.1159/000097451
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein in Umbilical Cord of Small-for-Gestational-Age Neonates

Abstract: Background: Several epidemiological studies reported a significant correlation between low birth weight and cardiovascular disease in adult life. Recent studies showed that an inflammatory response has been associated with the development of atherosclerosis. High-sensitivity C-reactive protein (hs-CRP) has been demonstrated to be a sensitive marker of this inflammatory process giving prognostic information in apparently healthy general population as well as in patients with symptomatic atherosclerosis.We hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
(12 reference statements)
1
32
2
Order By: Relevance
“…The production of TNF-a stimulates the apoptosis of placental trophoblasts associated with pregnancies complicated by IUGR. 7 Similar to our findings, Trevisanuto et al 12 showed that, in SGA infants, CRP concentrations are higher than those in AGA neonates, suggesting the presence of an inflammatory process in this group of patients during the fetal life.…”
Section: Discussionsupporting
confidence: 91%
“…The production of TNF-a stimulates the apoptosis of placental trophoblasts associated with pregnancies complicated by IUGR. 7 Similar to our findings, Trevisanuto et al 12 showed that, in SGA infants, CRP concentrations are higher than those in AGA neonates, suggesting the presence of an inflammatory process in this group of patients during the fetal life.…”
Section: Discussionsupporting
confidence: 91%
“…There are limited data on hsCRP and SGA. First-trimester levels of hsCRP were higher in gravidae with SGA (n ¼ 9) or preeclampsia (n ¼ 6) [27] or in cord blood from SGA neonates [28]. Given that systemic inflammation is increased with preeclampsia [20], one might also expect to find higher hsCRP.…”
Section: Discussionmentioning
confidence: 98%
“…Prior observational studies suggested that diets high in red meat, fatty dairy products, and refined carbohydrates were associated with increased CRP [5,31], while diets high in fiber correlated with lower levels [7,31]. Some [6,28] but not all [32,33] investigators reported that a high dietary glycemic index or load was associated with increased CRP, a relationship one study found only among the women [34]. When cholesterol intakes were increased for individuals on a National Cholesterol Education Step 1 diet, CRP levels rose in the lean participants with normal glucose tolerance but not in others [35].…”
Section: Discussionmentioning
confidence: 99%
“…For this follow-up phase of the study, we considered 50 children who had taken part in a previous investigational study on umbilical cord hs-CRP 7. Serum hs-CRP was obtained at birth from umbilical cord samples and measured by an immunonephelometric method (Dade Boehring, Marburg, Germany) applied to BN II (Dade Boehring) which employs polystyrene particles coated to monoclonal antibodies specific to human CRP.…”
Section: Methodsmentioning
confidence: 99%
“…At birth, high sensitivity-C reactive protein (hs-CRP), a prognostic marker for cardiovascular disease in apparently healthy middle aged subjects,5 6 is significantly higher in small for gestational age (SGA) infants in comparison with appropriate for gestational age (AGA) infants 7. These findings suggest the presence of early vascular damage, possibly due to an inflammatory mechanism.…”
mentioning
confidence: 99%